Association of variability in uric acid and future clinical outcomes of patient with coronary artery disease undergoing percutaneous coronary intervention. (March 2020) - Lim, Su Shen; Yang, Ya-Ling; Chen, Su-Chan; Wu, Cheng-Hsueh; Huang, Shao-Sung; Chan, Wan Leong; Lin, Shing-Jong; Chen, Jaw-Wen; Chou, Chia-Yu; Pan, Ju-Pin; Charng, Min-Ji; Chen, Ying-Hwa; et al.
Abstract: Background and aims: Hyperuricemia is independently associated with cardiovascular disease (CVD) and is considered to be one of the major risk factors for CVD. However, the impact of inter-visit uric acid (UA) variability on cardiovascular risk remains undetermined. Methods: We enrolled 3202 patients with coronary artery disease (CAD), who received successful coronary intervention, in a cohort from Taipei Veterans General Hospital from 2006 to 2015. All post-baseline visits UA measurements using standard deviation (SD) were analyzed to correlate with long-term outcome. The primary outcome was the composite of cardiac death, nonfatal MI, nonfatal stroke (MACE). The secondary event was MACE and hospitalization for heart failure. Results: During an average 65.06 ± 32.1-month follow-up, there were 66 cardiovascular deaths, 175 nonfatal myocardial infarctions, 64 nonfatal strokes, 287 hospitalizations for heart failure, and 683 revascularization procedures. There was a linear association between high UA SD and future adverse events. Compared to the lowest quartile SD, subjects in the highest quartile SD had a higher risk of MACE (HR: 2.53, 95% CI: 1.78–3.59), myocardial infarction (HR: 2.43, 95% CI: 1.53–3.86), cardiovascular death (HR: 6.45, 95% CI: 2.52–16.55), heart failure-related hospitalization (HR: 3.43, 95% CI: 2.32–5.05), and total major CV events (HR: 2.72, 95% CI: 2.09–3.56). Furthermore, compared to the average achieved on-treatment UA value, increasing UA SD had a stronger association of higher risk of developing MACE (HR: 1.51, 95% CI: 1.36–1.68), myocardial infarction (HR: 1.37, 95% CI: 1.38–1.68), ischemic stroke (HR: 1.43, 95% CI: 1.13–1.82), CV death (HR: 1.77, 95% CI: 1.50–2.11), HF (HR: 1.43, 95% CI: 1.29–1.58), and total major CV events (HR: 1.46, 95% CI: 1.34–1.58). Conclusions: High UA variability is associated with a higher risk of developing future cardiovascular events, suggesting the importance of maintaining stable serum UA levels and avoiding large fluctuations in CAD patients after percutaneous coronary intervention (PCI). Graphical abstract: Image 1 Highlights: High uric acid (UA) variability is associated with increased risk of developing future adverse outcome in coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI). Both higher UA variability and average UA value were significantly associated with a higher CV event occurrence. High UA variability had greater impact than high average UA value in patients with CAD.